Non-use of Janani Avam Bal Suraksha Yojana in a district of Bihar: ensuring safe deliveries needs strategy modification - Mukherjee, Madhumita; Singh, Rashmi; Mukherjee, Amrita; Bhattacharya, Madhulekha (International Journal Of Community Medicine And Public Health, 2018)
Background: India’s Janany Surakhsha Yojana (JSY) is the largest conditional cash transfer (CCT) program in the world in terms of the number of beneficiaries - covering about 9·5 million (36%) of 26 million women giving birth in India. Eleven States/UTs including Bihar, are still below the National estimate for institutional delivery of 78.9% (NFHS 4). In this study we attempted to find out the status of institutional and home deliveries in district Arwal of Bihar and reasons why in spite of cash incentives a proportion of mothers are opting for home delivery. Methods: A cross sectional descriptive design was used to interview 407 women, who had given birth to a child in previous one year. Focuss group discussions was held with community and health staff to corroborate the interview data. Results: Fifty nine percent of mothers were found to have preferred home delivery over institutional one. Reasons which came to light were home deliveries are cheaper (24.1%), unawareness about JSY (22%), unavailability of transport to reach hospital (22%) and better care being taken at home delivery (20.1%) variables. Older age, having a BPL card, and literacy of husband were found as favoring institutional delivery whereas dissatisfaction during a previous abortion or a livebirth in hospital were both associated with non-use. Conclusions: Better client awareness, strengthening of public health infrastructure, availability of skilled birth attendants at health subcentres (HSCs) and emergency transport in time can reduce number of home deliveries and lead to success of JBSY programme and subsequent reduction in maternal morbidity and mortality.